The COSMO-Spain Survey: Three First Rounds of the WHO Behavioral Insights Tool - Carmen Rodríguez-Blázquez; Carmen Rodríguez-Blázquez; María Romay-Barja; María Falcón; Alba Ayala; Alba Ayala; Maria João Forjaz; Maria João Forjaz (Frontiers Media S.A., 2021)
Objective: To describe changes in knowledge, attitudes and preventive practices (KAP), risk perception, and psychological variables of Spanish population toward the COVID-19 pandemic from July to November 2020.Methods: Three samples, each of one composed by 1,000+ persons aged 18 years or older, were interviewed online in three rounds, every 2 months, from July to November 2020.Results: The level of knowledge on COVID-19 was high in the three rounds, with percentages above 95% of correct answers related to ways of contagion and correct use of face masks. The most accepted measure was the mandatory use of face masks (80-86% of agreement in the three rounds, p = 0.001), followed by the night curfew (63% of agreement). Most participants (>80%) consistently reported using face masks, ventilating spaces, and washing or disinfecting hands. However, risk perception and self-efficacy were low. Worry about losing a loved one, the health system overload and people who do not wear face masks was high (>85% of the samples). The percentage of respondents who felt depressed due to COVID-19 increased from round 1 to round 3 (p = 0.044).Conclusions: Spanish population has a high degree of KAP, but a relatively low risk perception and self-efficacy. These findings can help health authorities to guide containment measures and campaigns addressed to improve preventive practices.